ANALISIS PENGARUH KARAKTERISTIK DISTRIBUTOR, DUKUNGAN PERUSAHAAN DAN ORGANISASI PEMBELAJARAN TERHADAP KINERJA DISTRIBUTOR MULTI LEVEL MARKETING (MLM) - Aqmala, Diana (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2011)
Salesperson plays an important role for the survival of the company. The role of salespeople in the Multi Level Marketing company is a distributor, which will promote products and  business plan. Distributor is very important because of the high competition between  companies  who also want to increase product sales. The key of success  in MLM companies depends on how the company is able to improve the performance of distributors. Problem of this research is how the characteristic  Distributors, companies support and organization  learning  affect the  performance of MLM distributors. Sampling technique used was purposive sampling method that used as many as 50 people  Tianshi distributors in Semarang. The results of data analysis showed that there is significant influence between the characteristic distributors, companies support and Organization  Learning  to the performance MLM distributor.